2006
DOI: 10.1016/j.surfcoat.2006.07.135
|View full text |Cite
|
Sign up to set email alerts
|

Influence of binder metal and surface treatment on the corrosion resistance of (W,Ti)C-based hardmetals

Abstract: The effect of a nitridation surface treatment on the microstructure and corrosion resistance of Co and Ni-binder (W,Ti)C-based hardmetals with additions of (Ta,Nb)C was investigated. Nitridation treatment produces a surface layer with a higher hard phase (Ti,Ta,Nb,W)(C,N) content. The near-surface layer thickness and microstructure are affected by the choice of binder (Co respectively Ni). The corrosion resistance of the hardmetals was characterized using linear sweep voltammetry. The microstructure of the har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…A second zone, known as a delamination area (labelled as ( 2)) can be seen, characterized by a loss of material in an area corresponding to a ring where the carbides are detached. As it is evident, the metallic binder suffers an anodic oxidation reaction and it is dissolved in the cutting fluid as previously reported for acid media [14,15,17]. This trend means that the effective leaching of the metallic phase takes place and thus, the onset of microcrack-like voids, in concordance with the work reported by Tarragó et al [8].…”
Section: Surface and Subsurface Damage Generated Under Monotonic And ...supporting
confidence: 87%
See 1 more Smart Citation
“…A second zone, known as a delamination area (labelled as ( 2)) can be seen, characterized by a loss of material in an area corresponding to a ring where the carbides are detached. As it is evident, the metallic binder suffers an anodic oxidation reaction and it is dissolved in the cutting fluid as previously reported for acid media [14,15,17]. This trend means that the effective leaching of the metallic phase takes place and thus, the onset of microcrack-like voids, in concordance with the work reported by Tarragó et al [8].…”
Section: Surface and Subsurface Damage Generated Under Monotonic And ...supporting
confidence: 87%
“…acid, caustic and neutral solutions as reported in Refs. [14][15][16][17][18][19]. However, these components usually work under cutting fluid and scarce information in this medium is available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…M A N U S C R I P T hardmetals has been extensively investigated in recent decades using different testing methodologies and addressing influence of multiple factors, such as surface state, corrosive medium, microstructural assemblage and binder chemical nature [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In these studies, it has been shown that: (1) corrosive media preferentially attack the binder phase when exposed to acidic and neutral environments; (2) in alkaline solution, the Co binder exhibits a stable passivation, while the WC phase dissolves easily; (3) damage by corrosion induced by acidic media is usually much more pronounced than that of neutral and basic ones; and (4) a greater amount of dissolution of the binder phase in acid solution eventually results in the formation of the oxide layer of W and a re gion depleted in Co, compared to the exposure in neutral and basic solutions.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Refs. [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. From these studies, several microstructural effects on corrosion response for these materials may be highlighted.…”
Section: Introductionmentioning
confidence: 99%